2014
DOI: 10.1007/s10047-014-0761-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and growth factor concentrations in activated platelet-rich plasma: a comparison of seven commercial separation systems

Abstract: Platelet-rich plasma (PRP) is blood plasma that has been enriched with platelets. It holds promise for clinical use in areas such as wound healing and regenerative medicine, including bone regeneration. This study characterized the composition of PRP produced by seven commercially available separation systems (JP200, GLO PRP, Magellan Autologous Platelet Separator System, KYOCERA Medical PRP Kit, SELPHYL, MyCells, and Dr. Shin's System THROMBO KIT) to evaluate the platelet, white blood cell, red blood cell, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 18 publications
3
99
2
2
Order By: Relevance
“…The production of PRP using a Selphyl device, described in the Kushida et al 16 study, furnished 0.21 billion injected platelets, whereas the Magellan device characterised in the same study furnished 5.43 billion injected platelets, corresponding to a 25-fold increase. The complete data are provided in table 2.…”
Section: Introductionmentioning
confidence: 93%
“…The production of PRP using a Selphyl device, described in the Kushida et al 16 study, furnished 0.21 billion injected platelets, whereas the Magellan device characterised in the same study furnished 5.43 billion injected platelets, corresponding to a 25-fold increase. The complete data are provided in table 2.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, different preparation methods aggravate the wide variability in the composition of different PRP products [13]. Kushida et al [14] reported great differences in growth factor concentrations in the activated PRP of seven commercial preparation systems. Mazzocca et al [15] examined three different PRP preparation methods regarding the concentration of platelets, red and white blood cells, and growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…PRP clearly has a concentration-dependent effect, with standardization of PRP preparation still unavailable. These factors and the numerous available protocols [74] can explain the contradictory results that have been obtained. More studies with a higher number of patients will be required to reach a consensus on the use of PRP at a defined concentration.…”
Section: Prp Enriched Graftsmentioning
confidence: 88%